Tradisi dan Pembaruan dalam Antologi Lengkap Cerpen A.A. Navis: Kajian Sosiologi Sastra - Irdawati Irdawati (Fakultas Bahasa dan Seni UNP, 2010)
The Complete Anthology of short stories written by AA Navis is the most complete collection of all short stories that have been written by Navis for fifty years of work. Based on a description and interpretation of data, theoretically, this study aims to (1) reveal the author's ideas and re-attempt the update against the ideologies of traditional Minangkabau society in ALCN which includes a description of Minangkabau culture, AA Navis with the process of creativity, as well as tradition and renewal, (2) develop and accumulate the research on the sociology of literature. Practically, this study aims to (1) provide advice and offers to the reader to constantly adapt and socialize to the demands and needs of the time by relying on rationality and morality, (2) provide an understanding of the short stories contained in ALCN. The research used the descriptive method of description of the facts followed by analysis of activities that include (1) forms the natural understanding of Minangkabau culture, AA Navis and authorship, (2) disclosure of Navis’ thoughts through theory and methods of sociological literature proposed by Swingewood Alan and Diana Laurenson, and (3) tradition and renewal efforts against traditional notions of ALCN. The results showed that the various ideas of Navis in ALCN are reflections of society psychological level and lead to a contradictive dialectical. Various complexity of community problems root on two things: (1) human nature is no longer guided by the nature, (2) the policy was decided without considering the principle of K4 (appropriateness and usefulness of togetherness and equality). Some thought the updates offered in ALCN are (1) awareness of human self to always adapt to the demands of the times, (2) implementation of worship should be interpreted rationally by humanitarian considerations, (3) renewal is a change in attitude towards a more humane and civilized; (4) acceptance of outside elements should be based on the principle of benefit and suitability, (5) philosophy stems renewal in humans and humanity, of nature as the basis for the interpretation and reasoning and rational thought. Key words: Nature, dialectical, religion, dan humanity